Experimentalist Regional Governance. Policy Analysis in Geographic-Functional Regions. - Sorg, Jens Matthias (Peter Lang, 2021)
Today, decision-making increasingly takes place in highly complex situations where the optimal solution is unclear upfront. If the decision-making process extends over several years - as in cases of large infrastructure projects - best available technologies, the group of people affected, and the institutions involved change over time. The presented research provides a decision-making concept for such situations. Based on a sound content analysis with over 400 documents and more than 31,000 pages, the regulatory structure of governance of the extension of Frankfurt Airport since the 1960s is analyzed. As a result, the theoretically derived concept of Experimentalist Regional Governance to analyze regulatory structures of governance in highly complex decision-making processes is confirmed.
Keywords: Regionalanalyse; Regional Governance; Entscheidungsstruktur; Flughafenausbau; Infrastrukturprojekt; Metropolregion; Entscheidungsprozess; Planungsbeteiligung; Institution; Empirische Untersuchung; Politikanalyse; Aktenanalyse; Experimentalist Governance